Schizophrenia with Obsessive Compulsive Symptoms: A Case Report - Jha, A; Joshi, D (Journal of Psychiatrists' Association of Nepal, 2019)
Obsessive-compulsive disorder/ symptoms may be co-morbid in schizophrenia. The clinical impact of this co-morbidity is poor response to anti-psychotic medications. We present a case of 35 yr old female who presented with symptoms suggestive of schizophrenia and later co-morbid obsessive symptom responded well to addition of fluoxetine to antipsychotics. This case study reveals that the identification and treatment of OCD in schizophrenia is very crucial for optimistic outcome.